Авиа, авиалбарын утга ба хүний анхны хэл: Meaning of sound and phoneme and human first language - Г., Буянтогтох (Mongolian Studies, 2023)
In this brief article, author discusses about Mongolian phonemes. According to the author, the phonemes are in a sense, such as morphemes, words and sentences. They are the first ancestral language or ancient speech.